A critical examination of the regulation of Ponzi scheme in Mauritius. Issue 6 (12th November 2018) - Uppiah, Valerie
Abstract : Purpose: The purpose of this paper is to analyse the regulation of the financial crime of Ponzi scheme in Mauritius. Contrary to money laundering which has a legal framework to combat it, for Ponzi scheme, there is no specific legal mechanism to combat this particular financial crime. Therefore, the aim of the paper is to provide for an analysis of Ponzi scheme which includes, inter alia, the definition of a Ponzi scheme, its modus operandi and how it should be tackled. Focus will be placed on devising a specific legal framework for it in Mauritius. Design/methodology/approach: The research method used to conduct this research and write this paper is a black letter legal research method. An analysis of several laws and cases is carried out so as to provide for the legal background of the research. Findings: The investigation conducted in this paper will lead to the conclusion that Mauritius has to devise a law which will specifically combat Ponzi schemes. This law shall provide for the ways to counter this financial crime as well as the duties of the various financial supervisory bodies. Originality/value: The paper provides for an analysis of the operation of Ponzi scheme in the Mauritian context. The paper also examines the existing legal framework that combats this financial crime in Mauritius and highlights its strengths and weaknesses.